The representation of cultural values in Korean as a foreign language (KFL) textbook - Samsudin, Didin; Ansas, Velayeti Nurfitriana; Triarisanti, Risa (Universitas Pendidikan Indonesia, 2021)
The representation of cultural values in textbooks is crucial to be examined because learning a foreign language is bound with the culture. Although previous research has quite extensively investigated this issue, much is yet to be explored in the context of Korean as a foreign language learning. This study aims to address the gap by investigating how cultural values are represented in the Korean as a foreign language (KFL) textbook, published by The Korea Foundation for Indonesians. A critical discourse analysis (CDA) approach was employed to analyze the data. The findings exhibited the representation of cultural values in four language skills: listening, speaking, reading, and writing. The introduction to the Korean language could be given through cultural recognition. Among the identified cultural values in the textbook, the representation of showing respect to creative products or the results of local culture was more evident than the other categories, followed by showing respect to cultural differences from various ethnic or religious groups and merging with nature and life. However, the representation category of showing respect to indigenous people’s culture was not seen in the textbook. This suggests that the textbook is intended to foster the students’ multicultural awareness in learning Korean as a foreign language.